1996
DOI: 10.1074/jbc.271.24.14271
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosation of Tryptophan Residue(s) in Serum Albumin and Model Dipeptides

Abstract: Nitrosation of bovine serum albumin with acidified NaNO 2 was compared to that of carboxymethyl-bovine serum albumin in which the thiol group is covalently blocked. Differential ultraviolet-visible (UV-Vis) spectroscopy and a modified Saville assay indicated that a non-cysteine residue(s) in carboxymethyl-bovine serum albumin was nitrosated. The nitrosated carboxymethylbovine serum albumin exhibited similar vasorelaxation activity as that observed with nitrosated bovine serum albumin. Identification of the nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 35 publications
(21 reference statements)
5
76
1
Order By: Relevance
“…In 1996 Zhang et al (32) studied the biological activity of N-nitrosated Gly-Trp and carboxymethyl bovine serum albumin (CM-BSA), a modified derivative in which the thiol group is covalently blocked, in comparison with GSNO. Because these data were a bit distorted by the nitroso content of the applied nitroso compounds, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1996 Zhang et al (32) studied the biological activity of N-nitrosated Gly-Trp and carboxymethyl bovine serum albumin (CM-BSA), a modified derivative in which the thiol group is covalently blocked, in comparison with GSNO. Because these data were a bit distorted by the nitroso content of the applied nitroso compounds, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the corrected data clearly demonstrate that the efficacy of the Gly-NO-Trp-induced vasorelaxation and the inhibition of platelet aggregation was nearly identical to that of GSNO. Because Gly-NO-Trp does not spontaneously diffuse through cellular membranes, Zhang et al (32) suggested that extracellular N-nitrosocompounds transfer the nitroso function via a transnitrosation reaction to a NO-carrier "located on or associated with the plasma membrane" (32). Assuming that a protein-bound cysteine is the NO carrier, which can indeed be highly effective in transporting nitric oxide through cellular membranes (23,24), the small peptide Gly-NO-Trp may induce such a process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In micellar oxidative nitrosation when the nitrosating agent is formed from NO and O 2 within hydrophobic phases, the carbon atoms of tryptophan residues embedded into the hydrophobic phase are supposed to be attacked much more efficiently than the nitrogen atom in a more hydrophilic surrounding. Moreover, it is well known that nitrosation of acylated derivatives of tryptophan proceeds via the C 3 [C(G)] atom and that the intramolecular rearrangement ON-C 3 → ON-N 1 is probably a rate-determining stage (16)(17)(18). The equilibrium constant for the formation of N -acetyl-N 1 -nitrosotryptophan in water was found to be 850 M −1 (18).…”
Section: Resultsmentioning
confidence: 99%
“…However, the nitroso-tryptophan fraction in proteins is usually small. NOW was detected in in vitro experiments upon nitrosation of serum albumin, and its functional activity as EDRF was demonstrated (16). The reaction of NOW denitrosation was previously studied using acetyl-N 1 -nitrosotryptophan (17,18).…”
Section: Introductionmentioning
confidence: 99%